2006
DOI: 10.1016/j.molcel.2006.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Key Interaction Modes of Dynamic +TIP Networks

Abstract: Dynamic microtubule plus-end tracking protein (+TIP) networks are implicated in all functions of microtubules, but the molecular determinants of their interactions are largely unknown. Here, we have explored key binding modes of +TIPs by analyzing the interactions between selected CAP-Gly, EB-like, and carboxy-terminal EEY/F-COO(-) sequence motifs. X-ray crystallography and biophysical binding studies demonstrate that the beta2-beta3 loop of CAP-Gly domains determines EB-like motif binding specificity. They fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
225
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(245 citation statements)
references
References 30 publications
19
225
1
Order By: Relevance
“…At the same time, as shown in Fig. 3D, loop regions in CAP-Gly underwent pronounced conformational changes upon the formation of a complex with MTs, compared with the free CAP-Gly and CAP-Gly/EB1 complex (15,23,26). These changes resulted in sidechains adopting different orientations in free and MTand EB1-bound states (Fig.…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations
“…At the same time, as shown in Fig. 3D, loop regions in CAP-Gly underwent pronounced conformational changes upon the formation of a complex with MTs, compared with the free CAP-Gly and CAP-Gly/EB1 complex (15,23,26). These changes resulted in sidechains adopting different orientations in free and MTand EB1-bound states (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…Fig. 1 illustrates a cosedimentation assay of a typical MAS NMR sample of the U-13 C, 15 N-CAP-Gly/MT complex; CAP-Gly-MT binding assays performed under different conditions are also presented in SI Appendix. The results are fully consistent with our prior findings (22), indicating that CAP-Gly/MT binding is specific and that the binding affinity is estimated in the micromolar range.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The critical dynactin subunit for plus‐end tracking is p150 Glued (called p150 here). Its N‐terminal CAP‐Gly domain protrudes from the shoulder of the dynactin complex (Chowdhury et al , 2015; Urnavicius et al , 2015) and binds directly to microtubules (Culver‐Hanlon et al , 2006; Peris et al , 1998; Ross et al , 2006), as well as to EBs (Honnappa et al , 2006). In vitro reconstitution experiments with a p150 fragment showed that the p150 CAP‐Gly domain and the first coiled‐coil of p150, which interacts with the intermediate chain of the dynein complex (Karki & Holzbaur, 1995; Vaughan & Vallee, 1995; King et al , 2003), were sufficient for mediating EB‐dependent end tracking of the human dynein complex (Duellberg et al , 2014).…”
Section: Introductionmentioning
confidence: 99%